DAMPAK KEBIJAKAN PENGALIHAN SUBSIDI BBM DI TENGAH KRISIS MULTINASIONAL TERHADAP INFLASI DAN PERTUMBUHAN EKONOMI DI INDONESIA - Harmono, Wahyu (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
The transfer of fuel subsidies of Indonesia’s State Budget (APBN) has been carried out several times with purpose to balance the ability of the government's State Budget in facing the challenges of the global economy. In the middle of Indonesia's economic recovery, the government re-implemented the transfer of fuel subsidies which was triggered by an increase in the price of crude oil commodities due to the geopolitical war between Russia and Ukraine. The limited capacity of the APBN and to improve the distributing of the subsidies, then Rp. 502.4 trillion of the subsidy budget allocation stipulated in Presidential Regulation 98 of 2022 has been diverted. The multiplier effect due to rising fuel prices which has the potential to increase other commodity prices resulting in a significant increase in national inflation and a slowdown in economic growth due to inflation are the main risks of this policy. Utilizing government fiscal instruments, as well as improve collaboration between institutions in the monetary sector (Indonesian Bank), the government of the Republic of Indonesia succeeded in implementing the transfer of fuel subsidies while maintaining the national inflation rate below 6 percent until November 2022 and maintaining the national economic growth rate in the third quarter of 2022.